ANALISIS POTENSI PARIWISATA DI PULAU KANGEAN - Asmaul Hayani; Idah Zuhroh; Sri Budi Cantika (Program Studi Ekonomi Pembangunan, 2020)
This study aims to analyze the tourism potential on Kangean Island as mandated by the Minister of Home Affairs Regulation No. 01 of 2007 explaining that recreational parks are one type of urban green open space (RTHKP). In the Law of the Republic of Indonesia No.10 of 2009 concerning tourism is a variety of facilities and services provided by stakeholders such as the community, entrepreneurs, local governments. Potential tourism in the Kangean islands based on natural tourism with the natural conditions and the quality of the beautiful beaches, this condition really has the opportunity to be developed into a tourist destination Kangean islands. The potential that exists in Kangean Island is identified through five aspects, namely: Uniqueness, diversity, natural wealth, beach quality, and beauty and to find out whether or not it is a tourism tourism area using SWOT analysts by looking at the strengths, weaknesses, opportunities and threats in each tourist spot.. The method used in this research is descriptive qualitative research, and the results of the study show that tourism in Kangean Island is feasible to be developed because its potential is very promising.